Epistemologi Tafsir, Ta’wil, dan Hermeneutika: Kajian Komparatif - Ilyas Supena (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2008)
These writing attempts to explain the epistemological construction of the methods of exegesis (tafsir), allegorical interpretation (ta’wīl), and hermeneutics. Epistemologically, several points can be put forward. Firstly, exegesis tends to emphasize an objectivist nature, based on a linguistic approach. On the other hand, allegorical interpretation tends to emphasize a subjectivist nature, relying on an intuitive and rational approach. Meanwhile, hermeneutics tends to emphasize an intersubjectivist nature, utilizing historical, sociological, and psychological approaches. Secondly, the source of knowledge according to exegesis is the text, whereas according to allegorical interpretation it is inner experience. Meanwhile, hermeneutics considers the source of knowledge to be the textual world, as well as the worlds of the author and the reader. Thirdly, the criterion for scholarly validity used in the tradition of exegesis is the similarity or closeness between the text and its meaning. In contrast, the criterion for scholarly validity used in the tradition of allegorical interpretation can only be directly sensed and experienced through intuition, taste (dzauq), or psycho-gnosis. Meanwhile, the criterion for scholarly validity used in the tradition of hermeneutics is more dialogical and dialectical, involving the interplay between the textual world, the world of the author, and the world of the reader.